The regulation of luteinizing hormone exocytosis in α-toxin permeabilized sheep anterior pituitary cells - Van der Merwe, Philip Anton (Division of Chemical Pathology, 2017)
Although exocytosis is the major mechanism by which cells secrete products into their environment, little is known about the mechanism of this fundamental process. Previous studies on the regulation of luteinizing hormone (LH) exocytosis have used intact cells exclusively. It is not possible, however, to determine the precise requirements for exocytosis in intact cells since the cytosol is not directly accessible. Permeabilization of the plasma membrane allows experimental manipulation of the intracellular milieu while preserving the exocytic apparatus. The diameter of the atoxin pores (2-3 nm) allowed the exchange of small molecules such as ATP while larger cytosolic proteins such as lactate dehydrogenase were retained. Because of the slow exchange of small molecules through a-toxin pores a protocol was developed which combines prolonged pre-equilibration of the permeabilized cells at 0°C before stimulation with strong Ca²⁺ buffering. Under these conditions an increase in the [Ca²⁺]free stimulated a 15-20 fold increase in LH exocytosis (EC₅₀ pCa 5.5). After 12-15 minutes the rate of exocytosis declined and the cells became refractory to Ca²⁺. At resting [Ca²⁺]free (pea 7), cAMP stimulated a rapid, 2 - 3 fold, increase in LH exocytosis. cAMP caused a modest enhancement of Ca²⁺-stimulated LH exocytosis by causing a left shift in the EC₅₀ for Ca²⁺ from pCa 5.6 to pCa 5.9. Activation of protein kinase C (PKC) with phorbol 12-myristate 13-acetate (PMA) synergistically enhanced cAMP-stimulated LH exocytosis, an effect which was further augmented by increasing the [Ca²⁺]free· Gonadotrophin-releasing hormone (GnRH) was found to stimulate cAMP production in intact pituitary cells. Since previous studies have shown that GnRH activates PKC and stimulates a rise in cytosolic [Ca²⁺]free, these results suggest that a synergistic interaction of the cAMP, PKC and Ca²⁺ second messenger systems is of importance in the mechanism of GnRH-stimulated LH exocytosis. When permeabilized cells were equilibrated for prolonged periods in the absence of MgATP, Ca²⁺-stimulated LH exocytosis declined. The time course of the decline closely followed the leakage of intracellular ¹⁴C-ATP. Addition of MgATP rapidly restored full Ca²⁺-stimulated LH exocytosis. Ca²⁺-, cAMP-, and PMA-stimulated LH exocytosis were all dependent on millimolar MgATP concentrations (EC₅₀ 1 .5-3 mM). It has been postulated that PKC is a mediator of Ca²⁺- stimulated exocytosis. Several findings in the present study argue against this hypothesis. Firstly, PMA and Ca²⁺ had additive effects on LH exocytosis at all [Ca²⁺]free· Secondly, PMA was able to stimulate further LH release from cells made refractory to high [Ca²⁺]free· Thirdly, the PKC inhibitor staurosporine did not inhibit Ca²⁺-stimulated LH exocytosis under conditions in which it inhibited PMAstimulated exocytosis. Fourthly, in cells desensitized to PMA by prolonged exposure to a high PMA concentrations, Ca²⁺-stimulated LH exocytosis was not inhibited. And finally, Ba²⁺+ was able to stimulate LH exocytosis to a maximal extent similar to Ca²⁺ despite the fact that Ba²⁺+ is an extremely poor activator of PKC. Since Ba²⁺+ is also a poor activator of calmodulin, this latter result implies that calmodulin does not mediate the effect of Ca²⁺. In agreement with this, the calmodulin inhibitor calmidazolium did not inhibit Ca²⁺-stimulated LH exocytosis. Since GTP-binding proteins have been implicated in regulated exocytosis in other cell systems, the effects of guanine nucleotides on LH exocytosis were examined. At resting cytosolic [Ca²⁺]free (pea 7), the GTP analogues GTPyS and GMPPNP stimulated LH exocytosis with similar potencies (EC₅₀ 20-50 μM). Additional experiments indicated that the effects of these GTP analogues could not be explained by activation of either PKC alone or cAMP-dependent protein kinase alone. In the presence of both PMA and cAMP, GMPPNP did not stimulate a further increase in the rate of LH exocytosis, suggesting that the stimulatory actions of guanine nucleotides may be mediated by the combined activation of PKC and generation of cAMP, as a result of activation of signal-transducing G proteins. In contrast, pretreatment of cells with GTPyS at low [Ca²⁺]free markedly inhibited subsequent responses to Ca²⁺, cAMP, PMA, and cAMP plus PMA. This inhibitory effect required lower GTPyS concentrations than the stimulatory effect (IC₅₀ 1-10 μM), and was not observed with GMPPNP. These findings indicate the involvement of a distinct guanine nucleotide-binding protein in exocytosis at a site distal to second messenger generation.